Rasionalisme dalam Perkembangan Ekonomi Mainstrim dan Islam di Indonesia - Nurizal Ismail; Siti Aisyah; Wahyudi Bakri (Universitas Darussalam Gontor, 2020)
Rationalism is one of the philosophical schools originated from Greek Civilization. Two prominent scholars developed the theory, namely Plato and Aristotle. The ratio is a crucial way to approach truth. The rationalism has influenced all knowledge and sciences developed by other scholars in different time and place. The study aims to know the influence of rationalism toward economic development in Indonesia. To obtain a clear answer, the study used thematic analysis to identify, categorize, and report the qualitative data related to the study. The finding says that rationalism has been adopted by Indonesia when it used either capitalism or socialism in the development of economic in Indonesia. The existence of Islamic economics in Indonesia gives a new paradigm of the method in understanding and solve the economic problem by using ratio in the framework of Islamic revelation. By then, there is a fundamental difference of philosophical underpinning related to the development of economic in Indonesia, starting from a conventional one to Islamic economics combining ratio and revelation to solve the economic problem of society.